Sterilizer chamber design with telegram-based internet of things (IoT) applications - Nurwijayanti Kusumaningrum; Reza Ananda (Institut Teknologi Dirgantara Adisutjipto, 2021)
In order to reduce the spread of the corona virus in office areas, malls or housing, a sterilizer chamber is installed. It is used to detect someone who will enter an area and he must be sterilized first by spraying the entire body with disinfectant liquid automatically. By combining the sterilizer chamber tool with IoT technology, the sterilizer chamber tool can be monitored continuously at a certain distance using a sensor as a detector which will provide information to one of the operators of the tool condition, about the remaining liquid, the number of people who have been sterilized. The system works by providing information on the liquid spray time of about 5 seconds and information on the liquid level in the tube from level 5-70. The average output pin voltage is 4.89 V when the sensor detects an obstacle in front of the sensor and the NODEMCU will receive a voltage 4.89 V from the output pin and ultrasonic sensor HC-SR04. The highest voltage reaches 673.2 Mv, when the distance to the object is 40 cm with the lowest voltage is 100.3 mV with the closest distance being 5 cm.